2D Material Enabled Offset‐Patterning with Atomic Resolution. (9th August 2020) - Chen, Szu‐Hua; Hofmann, Mario; Yen, Zhi‐Long; Hsieh, Ya‐Ping
Abstract: Atomic‐precision patterning at large scale is a central requirement for nanotechnology and future electronics that is hindered by the limitations of lithographical techniques. Historically, imperfections of the fabrication tools have been compensated by multi‐patterning using sequential lithography processes. The realization of nanometer‐scale features from much larger patterns through offset stacking of atomically thin masks is demonstrated. A unique mutual stabilization effect between two graphene layers produces atomically abrupt transitions that selectively expose single‐layer covered regions. Bilayer regions, on the other hand, protect the underlying substrate from removal for several hours permitting transfer of atomic thickness variations into lateral features in various semiconductors. Nanoscopic offsets between two 2D materials layers could be introduced through bottom‐up and top‐down approaches, opening up new routes for high‐resolution patterning. A self‐aligned templating approach yields nanometer‐wide bilayer graphene nanoribbons with macroscopic length that produces high‐aspect‐ratio silicon nanowalls. Moreover, offset‐transfer of lithographically patterned graphene layers enables multipatterning of large arrays of semiconductor features whose resolution is not limited by the employed lithography and could reach <10 nm feature size. The results open up a new route to combining design flexibility with unprecedented resolution at large scale. Abstract : The selective ability of bilayer graphene—both artificially and naturally produced to protect a substrate from plasma etching for extended periods permits the patterning of various semiconductors by mechanically offsetting two atomically thin masking layers. The produced arrays of the semiconductors exhibit dimensions in the sub‐10 nm scale and their dimensions are independent of the lithographical patterning resolution.